Confinement-based direct design of circular steel tube confined concrete (STCC) short columns. (May 2023) - Hassanein, M.F.; Hamed, Asmaa Y.; Shao, Yong-Bo; Silvestre, N.
Abstract: A new design model to estimate the axial compressive resistance of circular steel tube confined concrete (STCC) short columns is proposed in this paper. These STCC columns differ from standard concrete-filled steel tubular (CFST) columns because their concrete core carries all the compressive stresses (the steel tube is not compressed). The design model considers the confinement effect of the outer steel tube on the concrete core. The experimental test results of axially-loaded STCC short columns with normal, high and ultra-high strength concrete were first collected from the literature. The test resistances of the columns were then compared to the predictions obtained by EC4 (2004), ANSI/AISC (2010), AIJ (2001), ACI 318R (2014) and CISC (2007), as well as analytical design models presented in the literature. This comparative study indicated that most design codes are conservative, while most analytical design models are unconservative. Additionally, they do not keep the same accuracy level over the whole slenderness range of circular steel tubes. Then, the test resistances were used to propose and calibrate a new formula to evaluate the lateral confining pressure ( f rp ) provided by the steel tube to the concrete core of different grades. The f rp formula is used to propose a confinement-based direct resistance for axially-loaded circular STCC short columns. The results of the proposed design model are much better than those obtained from the available design predictions, regardless of the slenderness ratio of the steel tube and steel/concrete grades, which can also be used with stainless STCC short columns. Highlights: A confinement-based direct design model is developed for steel tube confined concrete (STCC) short columns. The experimental test results of axially-loaded STCC short columns were collected from the literature. All design codes as well as other design models were found to be highly conservative. All design codes do not have the same accuracy over the full range of steel tube slenderness.